HUBUNGAN KONDISI SOSIAL EKONOMI MASYARAKAT PETANI TERHADAP DEGRADASI LAHAN DI DAS ALO POHU PROVINSI GORONTALO - Moh Khamal Salote; Fitryane Lihawa; Iswan Dunggio (Universitas Negeri Gorontalo, 2022)
The purpose of the study was to analyze the socioeconomic conditions of the community and their relationship to land degradation in the Alo Pohu watershed, Gorontalo Province. The research method used in this study is a survey method with a total population of 79,828 people. The sampling method is a purposive sampling method with the criteria of people working as farmers determining the number of samples based on the Slovin formula, and the number of samples is 392 people. The socioeconomic parameters studied are education level, knowledge, income, household expenses, land ownership, and the number of dependents. In addition, perceptions and parameters of land degradation are determined based on the criticality level of the land. The data collection method is a questionnaire method. The data analysis used is quantitative and descriptive. A cross-table analyzes the relationship between socioeconomic conditions and land degradation. The results showed three socioeconomic parameters that significantly affected land degradation in the Alo Pohu watershed: education level, land ownership, and knowledge of critical land.